KEANEKARAGAMAN JENIS BURUNG DI HUTAN RAWA SAEMBAWALATI DESA TOMUI KARYA KECAMATAN MORI ATAS KABUPATEN MOROWALI - Watalee, Hiskia; Ningsih, Sri; Ramlah, Sitti (Jurnal Warta Rimba, 2013)
A bird is a wildlife which could be found almost in any vegetated environment. The existence of a bird in one area is very important because it could affect the presence and distribution of plant species. This study aims to determine species composition, attendance of birds, evennes, species diversity, and the dominance of birds in Saembawalati Swamp Forest. The study was conducted from April to June 2013. Data collection was carried out using line transect method. After conducting the research in Saembawalati swamp forest, it was found 34 species of birds from 15 families, swamp forest habitat tree vegetation zones have indeks values species diversity (H') = 2.75 and evenness (E) = 0.11 and swamp forest habitat zones has turf vegetation index values species diversity (H')=3.00 and evennes (E) = 0.10. There were four species of birds that are always found in the swamp forest of Saembawalati; Egretta garzetta, Gallinula chloropus, Phaenicophaeus calyorhynchus, and Amaurornis phoenicurus. Hence, Saembawalati swamp forest was dominated by four species of birds; Bubulcus ibis, Egretta garzetta, Dicrurus hottentottus, Phaenicophaeus calyorhynchus. Keywords: bird, diversity, Saembawalati swamp forest.